Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Bisnis Sepatu Wanita Online Shop Aci Stuff (Studi Kasus Importir Sepatu Wanita Aci Stuff) - Awanis, Adara; Noor, Laili Savitri; Hermawati, Ati (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2024)
The purpose of this study is to find out about analyzing marketing strategies to increase sales of women shoe business online shop Aci Stuff. The results of this study show that the online shop Aci Stuff is in quadrant IV growing and build of the nine matrix IE SWOT. It can use alternative marketing strategies, which are intensive strategies consisting of market penetration, which is the price of product that match K-Pop fashion trend and maintain relationship with supplier and distributor. The market development strategies consist of create website, and development digital marketing promotional media. As well as product development strategy, which are improvements in product and service quality.